Monitoring the cognitive load in competitive environments in professional women’s basketball - Fuster, Joan; Capdevila, Lluis; Caparros, Toni (Frontiers in Psychology, 2025)
This study aims to describe the dynamics of training loads during specific training sessions, to determine the possible differences among the metrics of Cognitive Load (CL), External Load (EL) and Internal Load (IL) between training sessions and to assess the possible relationship between the CL, EL and IL variables to completely monitor the athletes’ performance level. Ten professional female basketball players (age 26.45 ± 3.5 years) took part in this descriptive study throughout the second round of competition, completing a total of 11 competitive microcycles. The training sessions were classified according to the distance between the previous game and the next one (MD +/− X), making distinctions between MD + 2, MD-4, MD-3, MD-2 and MD-1. The following descriptive variables of the tasks were recorded: specificity, number of players, playing space, time pressure, decision-making and competitive stimulus. The analyzed variables were rate of perceived cognitive exertion (RPE Cog) and heart rate variability (HRV) for CL, total amount of high intensity actions (HI-T) and total sum of accelerations – decelerations (AD-T) for EL, and rate of perceived exertion (RPE) and summated heart rate zones (SHRZ) for IL. The load dynamics showed an increase in uncertainty throughout the microcycle, progressing from less to more specific, and a load distribution in which MD + 2 and MD-1 show the lowest values and MD-4, MD-3 and MD-2 the highest. Significant differences (p < 0.01) were found between sessions for all the analyzed variables. Possible relationships between the CL, EL and IL metrics were also established. This study shows the reality of a professional team, where the distance from the next match determines the dynamics of the workload, promoting an increase in uncertainty and specificity throughout the microcycle, thus causing an increase in cognitive load.